ANALISIS PENGENDALIAN PERSEDIAAN OBAT DENGAN METODE ABC DAN VEN DI INSTALASI FARMASI RUMAH SAKIT UMUM DAERAH TABANAN - Firmayanthi, Ayu Felia; Satrya Dewi, Dewa Ayu Putu; Arimbawa, Putu Eka (Bali International University, 2023)
Background : Inaccuracy on drug management under Pharmacy Installation causes a over stock or stock-out, which cause disrupts services. There are 33 different drugs are out of stock, leading in a decrease quality of service at Tabanan Public Hospital Pharmacy Installation. So, we require an ideal drug inventory management system on the form of ABC, VEN, EOQ, Safety Stock, and Reorder Point methods at Tabanan Public Hospital Pharmacy Installation as a method in inventory control. Purpose : This study aims to identify and analyze drug control at Tabanan Public Hospital Pharmacy Installation using the ABC, VEN, EOQ, SS, and ROP analytical methods. Method : Uses a quantitative descriptive approach with a cross sectional design at Tabanan Public Hospital Pharmacy Installation during January to December 2021. Result : The results of the study on the ABC value found that A group 75.14% investment value, B group 15.30%, and C group 9.56%. The result of VEN analysis 16.67% for V group, E group 77.06%, and N group 6.27%. AE category has the most drug items and investment value in Quarter I-IV. The results of the EOQ calculation found the difference in the budget value for the procurement of the top 10 drugs in hospitals with the EOQ calculation of Rp 642,836,931 (11%). The EOQ, SS and ROP values are directly proportional to drug demand, therefore the computation of SS must be implemented properly. Conclusion : To avoid expired drug stocks at Tabanan Public IFRS, the ABC, VEN, EOQ, SS, and ROP methods must constantly used as an alternative for controlling drug supplies. Keywords: Drug Control, ABC, VEN, Economic Order Quantity (EOQ), Reorder Point, Safety Stock.